Ter- dragon curve: a view in cordial and edge cordial labeling - A. A., Sathakathulla (International Journal of Applied Mathematical Research, 2014)
A fractal is a mathematical set that typically displays self-similar patterns. The Ter dragon curve is also a fractal in the family of ?3 curve in brain filling curve models. There are many in this family of curves but for my study I have considered this fractal curve.   This fractal has been considered as a graph and the same has been viewed under the cordial and edge cordial labeling to apply this curve with scope for further study. Keywords: Ter-Dragon Curve, Brain Filling Fractal, Cordial, Edge Cordial, Graph.